Japan’s Success Story in Fostering Collective Responsibility in Suicide Prevention: The Power of Unity - Adeoye, Moses Adeleke; Akinnubi, Paul Olaolu (Universitas Pendidikan Indonesia (Indonesia University of Education), 2023)
Drawing insights from Japan’s inspiring initiatives, this article uncovers the valuable lessons that can be learned in addressing suicide issues with collective responsibility. This study attempts to investigate the importance of cooperation in Japan’s effectiveness in promoting collective responsibility for suicide prevention. Suicide is a significant public health issue around the world, and Japan has historically had high suicide rates. However, by employing several initiatives that prioritize shared responsibility and community involvement, Japan has recently achieved impressive strides in reducing suicide rates. This paper analyzes the crucial elements such as cultural elements, social support networks, and government initiatives that have contributed to Japan’s success. It also looks at how these strategies affect suicide prevention and emphasizes the lessons that other countries can learn from Japan’s experience. According to the study’s findings, the power of unity in combination with targeted therapy can effectively address the challenging issue of suicide prevention.